Cdkal1, a type 2 diabetes susceptibility gene, regulates mitochondrial function in adipose tissue - Colin J. Palmer; Raphael J. Bruckner; Joao A. Paulo; Lawrence Kazak; Jonathan Z. Long; Amir I. Mina; Zhaoming Deng; Katherine B. LeClair; Jessica A. Hall; Shangyu Hong; Peter-James H. Zushin; Kyle L. Smith; et al. (Elsevier, 2017)
Objectives: Understanding how loci identified by genome wide association studies (GWAS) contribute to pathogenesis requires new mechanistic insights. Variants within CDKAL1 are strongly linked to an increased risk of developing type 2 diabetes and obesity. Investigations in mouse models have focused on the function of Cdkal1 as a tRNALys modifier and downstream effects of Cdkal1 loss on pro-insulin translational fidelity in pancreatic β−cells. However, Cdkal1 is broadly expressed in other metabolically relevant tissues, including adipose tissue. In addition, the Cdkal1 homolog Cdk5rap1 regulates mitochondrial protein translation and mitochondrial function in skeletal muscle. We tested whether adipocyte-specific Cdkal1 deletion alters systemic glucose homeostasis or adipose mitochondrial function independently of its effects on pro-insulin translation and insulin secretion. Methods: We measured mRNA levels of type 2 diabetes GWAS genes, including Cdkal1, in adipose tissue from lean and obese mice. We then established a mouse model with adipocyte-specific Cdkal1 deletion. We examined the effects of adipose Cdkal1 deletion using indirect calorimetry on mice during a cold temperature challenge, as well as by measuring cellular and mitochondrial respiration in vitro. We also examined brown adipose tissue (BAT) mitochondrial morphology by electron microscopy. Utilizing co-immunoprecipitation followed by mass spectrometry, we performed interaction mapping to identify new CDKAL1 binding partners. Furthermore, we tested whether Cdkal1 loss in adipose tissue affects total protein levels or accurate Lys incorporation by tRNALys using quantitative mass spectrometry. Results: We found that Cdkal1 mRNA levels are reduced in adipose tissue of obese mice. Using adipose-specific Cdkal1 KO mice (A-KO), we demonstrated that mitochondrial function is impaired in primary differentiated brown adipocytes and in isolated mitochondria from A-KO brown adipose tissue. A-KO mice displayed decreased energy expenditure during 4 °C cold challenge. Furthermore, mitochondrial morphology was highly abnormal in A-KO BAT. Surprisingly, we found that lysine codon representation was unchanged in Cdkal1 A-KO adipose tissue. We identified novel protein interactors of CDKAL1, including SLC25A4/ANT1, an inner mitochondrial membrane ADP/ATP translocator. ANT proteins can account for the UCP1-independent basal proton leak in BAT mitochondria. Cdkal1 A-KO mice had increased ANT1 protein levels in their white adipose tissue. Conclusions: Cdkal1 is necessary for normal mitochondrial morphology and function in adipose tissue. These results suggest that the type 2 diabetes susceptibility gene CDKAL1 has novel functions in regulating mitochondrial activity.